PENGUJIAN MODEL PRISTIANTO UNTUK MEMPREDIKSI LAJU INFILTRASI DI SUB DAS KLAWALAL KELURAHAN MAKOTYAMSA - Hendrik Pristianto; Asrul Saputra; Fatimah Putri Maharani; Achmad Rusdi; Ahmad Januar Jafaruddin (Jurnal Teknik Sipil : Rancang Bangun, 2025)
Infiltration is the process of water entering the soil and plays a vital role in groundwater recharge, flood control, and water resource management. A decrease in infiltration rate due to land use changes has become a serious concern, especially in small watersheds such as the Klawalal Sub-Watershed in Makotyamsa. The Pristianto Model was developed to predict infiltration rates in small watersheds by modifying the Kostiakov Model with the addition of soil moisture, porosity, and sand content variables, making it more suitable for local conditions. This study aims to evaluate the performance of the Pristianto Model at six observation points with soil texture variations including Sandy Loam, Clay Loam, and Sandy Clay Loam. Field data were collected using the double ring infiltrometer method, supported by laboratory testing of physical soil properties. The model was validated using graphical analysis and statistical evaluation with NSE and RSR indicators. The results showed that the Pristianto Model successfully predicted infiltration rates at most observation points. With NSE values > 0.75 and RSR < 0.5, the model demonstrated high accuracy. Therefore, the Pristianto Model is recommended as a predictive tool for infiltration rates in small watersheds with similar characteristics.